2016
DOI: 10.1002/anie.201601252
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Room‐Temperature‐Phosphorescent Materials Prepared from N‐Substituted Naphthalimides: Emission Enhancement and Chemical Conjugation

Abstract: Purely organic materials with room-temperature phosphorescence (RTP) are currently under intense investigation because of their potential applications in sensing, imaging, and displaying. Inspired by certain organometallic systems, where ligand-localized phosphorescence ((3) π-π*) is mediated by ligand-to-metal or metal-to-ligand charge transfer (CT) states, we now show that donor-to-acceptor CT states from the same organic molecule can also mediate π-localized RTP. In the model system of N-substituted naphtha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
255
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 391 publications
(265 citation statements)
references
References 28 publications
6
255
0
Order By: Relevance
“…[12] Theoretical Verification of CBT-Induced ISC To elucidate the mechanism of ultra-efficient ISC in PE3 and PE4, we carried out time-dependent density functional theory (TD-DFT) calculations of the singlet and the triplet excited states.A ccording to perturbation theory,asmaller singlet-triplet energy gap (DE ST )a nd greater spin-orbit coupling (SOC) constants facilitate higher F ISC . [12] Theoretical Verification of CBT-Induced ISC To elucidate the mechanism of ultra-efficient ISC in PE3 and PE4, we carried out time-dependent density functional theory (TD-DFT) calculations of the singlet and the triplet excited states.A ccording to perturbation theory,asmaller singlet-triplet energy gap (DE ST )a nd greater spin-orbit coupling (SOC) constants facilitate higher F ISC .…”
Section: Quantification Of Iscmentioning
confidence: 99%
“…[12] Theoretical Verification of CBT-Induced ISC To elucidate the mechanism of ultra-efficient ISC in PE3 and PE4, we carried out time-dependent density functional theory (TD-DFT) calculations of the singlet and the triplet excited states.A ccording to perturbation theory,asmaller singlet-triplet energy gap (DE ST )a nd greater spin-orbit coupling (SOC) constants facilitate higher F ISC . [12] Theoretical Verification of CBT-Induced ISC To elucidate the mechanism of ultra-efficient ISC in PE3 and PE4, we carried out time-dependent density functional theory (TD-DFT) calculations of the singlet and the triplet excited states.A ccording to perturbation theory,asmaller singlet-triplet energy gap (DE ST )a nd greater spin-orbit coupling (SOC) constants facilitate higher F ISC .…”
Section: Quantification Of Iscmentioning
confidence: 99%
“…RTP of a polymethylmethacrylate film incorporating 0.5% N-aryl naphthalimide derivative (31) was attributed to an intramolecular CT transition by G. Zhang, et al 36 The small energy gap between 1 CT and 3 CT was suggested to be a cause of the enhanced ISC. This hypothesis was supported by the fact that an N-alkyl derivative (32), a non-CT compound, did not show RTP.…”
Section: Other Phosphorescent Organic Solids and Their Mechanismsmentioning
confidence: 99%
“…Moreover, RTP materials have a potential application in encryption ink [15]. Generally speaking, organometallic molecules may more easily exhibit RTP properties, because heavy metal ions enhance spin-orbit coupling or decrease the small energy gap between singlet and triple states caused by charge transfer of metal to ligand (MLCT) or ligand to metal (LMCT) [16]. However, organometallic materials face some difficulties in application, due to their toxicity and instability in aqueous conditions.…”
Section: Introductionmentioning
confidence: 99%